New trends of development of beer industry in Lithuania – diversification and social responsibility - Petraškevičius, Vladislavas; Nedelko, Zlatko (Business, Management and Economics Engineering, 2017)
The main purpose of this article is to outline the current challenges of beer industry in Lithuania and provide suggestions for future development of organizations in this industry, by focusing on diversification strategy and social responsibility. The main challenges of Lithuanian beer industry are related to finding ways of future development in a constantly contracting market, as well as to find a competitive strategy of market penetration. In connection of these challenges, product differentiation creates new benefits for the consumers. However this strategy proves itself not being sufficient to reach the desired goals. Diversification of portfolio, being more risky, gives opportunity to target new customer groups and increase market presence. However, both strategies are less effective without changing the culture of drinking and consumer perceptions of beer. These issues will be addressed through the lenses of social responsibility, by emphasizing the promotion of responsible alcohol consumption and responsible behaviour of beer industry. As a result, the customers have to be ready to pay higher price for new products and develop a more responsible culture of beer consumption. To overcome outlined challenges, organizations in Lithuanian beer industry, must rethink their existing strategies and operations. Based on proposed future directions, the paper provides suggestions for business practices, how to implement differentiation strategy and actions in order to increase the level of social responsibility of various stakeholders.